Are Trabecular Metal Cones a Valid Option to Treat Metaphyseal Bone Defects in Complex Primary and Revision Knee Arthroplasty? - Bonanzinga, Tommaso; Gehrke, Thorsten; Zahar, Akos; Zaffagnini, Stefano; Marcacci, Maurilio; Haasper, Carl (Joints, 2018)
Purpose Metaphyseal bone defects are a challenge in complex primary and revision total knee arthroplasty (TKA). Recently, several studies have been published with promising results about the use of Trabecular Metal (TM) cones to address bone defects. The aim of this study is to review the literature to assess the efficacy of TM cones to address metaphyseal bone loss.Methods A comprehensive search was performed on PubMed, Medline, CINAHL, Cochrane, Embase, and Google Scholar databases using various combinations of the following keywords: “metaphyseal,” “cones,” “tantalum,” “knee,” and “revision.” Only papers reporting clinical data about the use of trabecular metal cones were included in the analysis. In vitro studies, case reports, surgical technique, or other studies where it was not possible to collect clinical data were excluded. Patients characteristics, details of the surgical procedures, outcome, and complications were collected from each included study.Results No controlled studies were available in the literature and all the papers were case series. In 16 studies included, the records of 442 patients with 447 implants and 523 TM cones were reported. The mean follow-up was 42 months (range: 5–105) for 360 procedures. Among 437 procedures, 30.4% were septic revisions. The Anderson Orthopaedic Research Institute (AORI) classification was available for 352 defects: 13 type 1, 69 type 2A, 115 type 2B, and 155 type 3. To manage these 352 defects, 360 TM cones were implanted. Intraoperative fractures occurred 13 times (10 femoral/3 tibial), 6 required surgical fixation. The overall infection rate was 7.38%, and the infection rate for the aseptic procedures was 0.99%. An aseptic exchange was performed 13 times, among these procedures two TM cones were loose. Signs of loosening were found just in 1.3% of the 523 TM cones implanted (5 femoral/2 tibial) during 447 procedures.Conclusion The TM cones are an effective solution to manage bone defects in complex primary and revision TKA at intermediate follow-up. The incidence of complications was low; however, the femoral metaphysis proved to be more susceptible to complications.Level of Evidence Level IV, systematic review of level IV studies.
Keywords: metaphyseal; cones; tantalum; knee; revision